IMPLEMENTATION OF MOBILE APPLICATION ‘SMARTSEA UNAIR’ TO INCREASE SALES PRODUCT FOR FISHERMEN IN MUNCAR DISTRICT, BANYUWANGI REGENCY - Nuraini, Siti; Nirmala, Dwitha; Millati, Izzato; Sagita, Ahmad Danang; Faroha, Shinta Nailul; Yurista, Weda (Universitas Airlangga, 2025)
The community service initiative conducted in Muncar District, Banyuwangi Regency, aim to address a fundamental issue: the limited market access faced by local fishermen. This initiative aligns with the goals of sustainable development, particularly in promoting decent work opportunities and robust economic growth. Enhancing market access is expected to increase fishermen’s incomes, thereby helping to reduce poverty in the fisheries sector. The Participatory Action Research (PAR) method was deemed appropriate for addressing the issues faced by 15 fishing partners. The initial steps included field observations and focus group discussions (FGDs) with seven partners to identify the core problems. To address these challenges, the community service team proposed the use of a mobile application called SmartSea Unair. This app is intended to improve the effectiveness of fish marketing. Initial evaluations using pre-tests (48%) and post-tests (52%) indicated an increase in the partners' knowledge. Further results, gathered through interviews with one of the partners, revealed that SmartSea Unair not only enhanced the fishermen families understanding but also delivered broader benefits. Notably, the app enabled partners to directly sell their fishery products to consumers outside of Java Island.